Morphological and Mechanical Effects in Sprague Dawley Rats Subjected to Hypoxia Cycles [Efectos Morfológicos y Mecánicos en Ratas Sprague Dawley Sometidas a Ciclos de Hipoxia] - Garcia-Herrera, C (Universidad de la Frontera, 2019)
SUMMARY: Extensive periods of hypoxic cause adaptive changes that make it possible to respond to the demands imposed by the environment. However, there are cases where this exposure is intermittent, as is the case of workers in andean areas. The objective of this communication was to verify the morphological and mechanical effects on diaphragm and lungs of rats subjected to intermittent hypoxic. Four 6-month-old Sprague Dawley rats were used. Two rats were subjected to 10 cycles of intermittent hypobaric hypoxic (IHH) of 96 h (~428 torr, PO2 90 mm Hg), followed by 96 h of normobaric normoxia, for 80 days. Uniaxial traction and staining tests were performed with Hematoxylin-Eosin and Picrosirius red de Junqueira. When comparing the curves of the diaphragms, those subjected to hypoxic slightly reduce their effort with respect to the condition of normoxia, in the lung tissue the hypoxic negatively affects its resistance, these show a lower slope with respect to the normoxics. In the histological analysis, the pulmonary parenchyma had a lower number of blood vessels and cellularity, such as a greater area fraction of alveolar spaces and amount of total collagen in IHH group. In the diaphragm, IHH group had a lower number of irregularly distributed myocytes and a lower amount of total collagen. In conclusion, the main findings indicate that the diaphragm and lung tissue subjected to IHH undergo structural changes, which result in a decrease in tensile strength. © 2019, Universidad de la Frontera. All rights reserved.